Pendampingan Pengenalan Proses Editing Terbitan Media Cetak Linggau Pos pada Mahasiswa Universitas PGRI Silampari - Tri Astuti; Nur Nisai Muslihah; Jamaludin Jamaludin; Susandra Susandra; Siti Anisah (LP4MK STKIP PGRI Lubuklinggau, 2025)
The ultimate goal of implementing this PKM is to educate students so that they gain direct experience in the form of practical knowledge about the editing process and the application of effective editing techniques. In addition, this activity also aims to broaden students' horizons about the development of the media industry and open up opportunities for collaboration between universities and the media. This is in line with the goal of achieving the Main Performance Indicators (IKU) 2 of higher education institutions, namely improving the quality of learning and graduate competencies through learning to gain experience outside the campus by involving experienced practitioners. The implementation of the activity was carried out for two weeks, namely at the end of February to early March 2025 at the Linggau Pos Daily office. The form of mentoring activities was in the form of counseling and socialization by implementing lecture, question and answer, and discussion methods. The target or participants in the PKM activity were 29 students in the fifth semester of the Indonesian Language and Literature Education study program. Initial findings from the results of the analysis of question and answer data with the director of the Linggau Pos daily, he welcomed this activity. According to his observations so far, many graduates or alumni of universities are still lacking in practical experience related to the world of work. Resulting in graduates being less ready to enter the world of work. After the PKM activity program was carried out, students realized the importance of gaining direct experience that could link the theories they got in college with real practices in the workplace. The results of the student response questionnaire on the activities carried out were 7.93% of students who responded as normal or quite good, 38.97% who responded as good and appropriate, and 53.10% who responded as very good or very appropriate.